Measurement of exclusive ρ 770 0 photoproduction in ultraperipheral pPb collisions at s NN = 5.02 Te - Sirunyan, A M; Tumasyan, A; Adam, W; Ambrogi, F; Asilar, E; Bergauer, T; Brandstetter, J; Dragicevic, M; Erö, J; Del Valle, A Escalante; Flechl, M; Frühwirth, R; et al. (The European physical journal. C, Particles and fields, 2019)
Exclusive ρ 770 0 photoproduction is measured for the first time in ultraperipheral pPb collisions at s NN = 5.02 Te with the CMS detector. The cross section σ ( γ p → ρ 770 0 p ) is 11.0 ± 1.4 (stat) ± 1.0 (syst) μ b at ⟨ W γ p ⟩ = 92.6 Ge for photon-proton centre-of-mass energies W γ p between 29 and 213 Ge . The differential cross section d σ / d | t | is measured in the interval 0.025 < | t | < 1 Ge 2 as a function of W γ p , where t is the squared four-momentum transfer at the proton vertex. The results are compared with previous measurements and theoretical predictions. The measured cross section σ ( γ p → ρ 770 0 p ) has a power-law dependence on the photon-proton centre-of-mass, consistent with electron-proton collision measurements performed at HERA. The W γ p dependence of the exponential slope of the differential cross section d σ / d | t | is also measured.